MODERN PSYCHOLOGICAL-PEDAGOGICAL APPROACHES AND TECHNOLOGIES IN SUPPORTING THE EDUCATIONAL PROCESS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The rapid development of educational systems worldwide requires the integration of modern psychological and pedagogical approaches and technologies to support the teaching-learning process. This thesis explores contemporary methodologies in educational psychology and pedagogy, focusing on their impact on student engagement, learning outcomes, and overall development. It examines innovative technological tools, such as digital platforms, adaptive learning systems, and gamification, and discusses their role in enhancing the educational experience. The paper also delves into the significance of individualized teaching methods, emotional intelligence, and collaborative learning in the modern classroom. Furthermore, it presents an overview of how these modern approaches contribute to creating inclusive, effective, and student-centered learning environments. The integration of technology, combined with solid psychological principles, promises to improve learning effectiveness and promote positive educational outcomes.